(untitled) (Global Journal of Management and Business Research, 2021)
The paper examines the perceptions of consumers towards online shopping. Population of the study was restricted to customers who prefer and to those who do not prefer online shopping in UAE. As exact population is unknown here ,the research has used Krejcie and Morgan formula of sample size calculation for infinite (unknown) Population. A sample of 100 customers has been taken for the study. Samples were selected as per convenience sampling method. Chi square test and Proportional test has been used to analyse the data. The analysis reveals that majority of the customers prefer manual shopping to online shopping. The analysis was done to find out the various barriers of online shopping and the factors effecting the perception of the customers towards online shopping.